Pears for sale in Rovaniemi, Finland in June 2018 ... - Campbell, Sandy (University of Alberta Library, 2018)
These pears from Holland were for sale in Rovaniemi, Finland in June, 2018. They were priced at 2.59 Euros/ kilo or approximately $3.94 CAD/kilo. The pears are of a variety known as Conference. ...